A bidirectional hybrid switched inductor converter with wide voltage conversion range. Issue 10 (1st June 2021) - Hulea, Dan; Cornea, Octavian; Muntean, Nicolae; Fahimi, Babak
Abstract: A bidirectional hybrid switched inductor converter (BHSI) is proposed in this paper. The converter uses an inductor switching cell in order to achieve a wide voltage conversion range, smaller passive components, and lower stress on the active devices. Apart from these advantages, the introduction of the additional inductor in the switching cell does not increase the complexity of the control structure, as is usually the case with other topologies with multiple components. The BHSI is compared, in terms of inductor/capacitor energies and total device stress, to other state‐of‐the‐art topologies and its advantages are highlighted. Two 3 kW prototypes were built, using Si‐MOSFETs and GaN‐FETs, in order to analyse their performances from the efficiency point of view, and to validate the theoretical findings. The stability analysis of the converter is performed and tested in a supercapacitor storage application, resulting in a good operation in both charge and discharge modes.